Rheumatic manifestations of endocrine diseases: skeletal diseases in hypoparathyroidism - Viktoria Georgiyevna Barskova; S A Vladimirov; A G Bochkova; F M Kudaeva; A V Smirnov; L A Bozhyeva; E L Nasonov (Современная ревматология, 2013)
Parathyroid diseases cause serious musculoskeletal problems. The major function of parathyroid hormone (PTH) is to regulate calcium levels in the body, which is closely related to vitamin D. PTH exerts a double (anabolic and catabolic) effect on the human skeleton, which accounts for its heterogeneous action on the bone and for the major clinical manifestations of diseases associated with its hyper- and hypoproduction. The paper considers the main causes of hypoparathyroidism (HPT) that is considered to mean inadequate PHT activity and/or secretion; moreover, the level of ionized calcium falls below the reference range. It describes two HPT cases that show the clinical picture resembling ankylosing spondylitis.